1981
DOI: 10.1111/j.1502-3885.1981.tb00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Diatom changes in sediments of basins possessing marine/lacustrine transitions in Frosta, Nord‐Trøndelag, Norway

Abstract: Diatoms in lower sediments from eight basins of the Frosta peninsula, Nord‐Trødelag, Norway, have been analysed. All the basins have been isolated from the sea, and a succession from a flora influenced by marine and brackish water to a freshwater flora is always found. An attempt is made to establish a relative salinity range for the fjord basin around the investigated area, from the Younger Dryas chronozone to the end of the Atlantic chronozone. These changes seem to be controlled by the accumulation and abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 5 publications
2
24
0
Order By: Relevance
“…Several of the deposits east of the Tautra-line are here thought to have been deposited in the Younger Dryas Chronozone (semu Mangerud et al 1974) and not within the Preboreal Chronozone as suggested by Sollid (1976). This development, which seems to be comparable with the history of the Oslofjord area (Sarensen 1979), was also indicated by Kjemperud (1981b). In a description of the Quaternary map of Trondheim (Reite 1983), the deglaciation and shoreline displacement are discussed.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Several of the deposits east of the Tautra-line are here thought to have been deposited in the Younger Dryas Chronozone (semu Mangerud et al 1974) and not within the Preboreal Chronozone as suggested by Sollid (1976). This development, which seems to be comparable with the history of the Oslofjord area (Sarensen 1979), was also indicated by Kjemperud (1981b). In a description of the Quaternary map of Trondheim (Reite 1983), the deglaciation and shoreline displacement are discussed.…”
supporting
confidence: 69%
“…This paper summarizes the main results of shoreline displacement investigations from four different sites (Figs. 1 and 2): Frosta (Kjemperud 1981a(Kjemperud , 1981b, Bjugn, Fr0ya and Hitra (Kjemperud 1982). A correlation of these data is attempted, and the regional pattern of relative uplift is lined out.…”
mentioning
confidence: 99%
“…Hafsten 1960;Kjemperud 1981;Long et al 2011) to reconstruct former relative sea levels. Hafsten 1960;Kjemperud 1981;Long et al 2011) to reconstruct former relative sea levels.…”
Section: Isolation Basins and Sill Considerationsmentioning
confidence: 99%
“…It is nevertheless predominantly a true benthic form with optimal growth conditions at salinity levels between 25 and 35% (Molder and Tynni, 1967), only becoming planktonic when forcibly detached from the bed, especially by storms in winter and autumn. Kjemperud (1981) has argued that frequencies in excess of 45% indicate the local presence of saline conditions. A frequency of 67% and its association with other polyhalobous taxa are therefore strongly indicative of a marine influence at the site, and therefore a marine origin for the sand layer.…”
Section: Radiocarbon Datingmentioning
confidence: 99%